2017
DOI: 10.1002/iid3.179
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of oncogenes expression in NK cells in patients with cancer

Abstract: IntroductionC‐kit/SCF signaling plays a key role in regulating NK cell homeostasis, maturation, proliferation, and cytotoxicity. C‐kit‐deficiency in NK cells results in significant reduction of their number, suggesting an imperative role for c‐kit signaling in NK cell biology. We have recently showed that human NK cells express not only c‐kit‐receptor, but also both membrane‐bound and soluble forms of c‐kit ligand—Stem cell factor. The goal of this study was to characterize the c‐kit/SCF autocrine loop in peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…The present studies have revealed that mast cells have a pro-tumor or anti-tumor role depending on the type of cancer, the degree of tumor progression, and the location of these immune cells in the tumor site [43]. The natural killer (NK) cells were discovered for their ability to rapidly recognize and efficiently kill tumor cells [44], and to release a number of cytokines that regulate both innate and adaptive immune responses [45]. The infiltration of NK cells in TME was associated with improved prognosis in triple-negative breast cancer [46] and colorectal cancer [47].…”
Section: Discussionmentioning
confidence: 99%
“…The present studies have revealed that mast cells have a pro-tumor or anti-tumor role depending on the type of cancer, the degree of tumor progression, and the location of these immune cells in the tumor site [43]. The natural killer (NK) cells were discovered for their ability to rapidly recognize and efficiently kill tumor cells [44], and to release a number of cytokines that regulate both innate and adaptive immune responses [45]. The infiltration of NK cells in TME was associated with improved prognosis in triple-negative breast cancer [46] and colorectal cancer [47].…”
Section: Discussionmentioning
confidence: 99%
“…c-Myc expression was significantly decreased in NK cells in all cancer patients independently of tumor location, stage of disease or the presence of metastases. 73 Marked changes in the expression of other oncogenes, such as c-kit, STAT3 and soluble and membrane-bound forms of ligand for c-kit/stem cell factor (SCF), were also found in these NK cells. c-Kit expression in NK cells was significantly decreased in all patients.…”
Section: Oncogenes and Transcription Factors As Regulators Of Immune mentioning
confidence: 99%
“…Expression of SCF had a clear tendency to be decreased, as well as c-kit did. 73 Alterations of the c-kit/SCF autocrine loop in NK cells in cancer seem indicated. In contrast, STAT3 expression in NK cells was significantly increased in lung cancer patients compared to healthy control donors.…”
Section: Oncogenes and Transcription Factors As Regulators Of Immune mentioning
confidence: 99%
“…Commercially available NanoFlares have also been used successfully by a number of groups for studying genetic content in live cells …”
Section: Hybridization‐based Probesmentioning
confidence: 99%